THE EFFECTIVENESS OF APPLYING SURROUND VISION EXERCISES AND VISUAL TRACKING IN IMPROVING MENTAL ROTATION AND DEVELOPING THE SKILL PERFORMANCE OF FUTSAL PLAYERS - Muhammad Saadoun Karim; Sadiq Jaafar Sadiq (Galaxy International Interdisciplinary Research Journal, 2023)
The objective of the study was to create visual exercises for peripheral vision and visual tracking, designed by the researcher, with the purpose of enhancing the mental rotation and skill performance of futsal players. Additionally, the study aimed to determine the extent of improvement observed in the research group. The researcher posited multiple hypotheses, one of which was that there would be statistically significant differences between the pre-test and post-test results across all research variables. As the researcher employed the experimental method for the two equivalent experimental and control groups with pre- and post-tests due to the research problem’s experimental nature, the total number of the research sample (27) players. The duration of the application of the main research experiment was eleven weeks, and by using two educational units per week, a total of twenty-two educational units were utilised during the application of the main research experiment. After the main experiment was applied, post-tests were conducted for the variables of the research under study and for the experimental and control groups. The exercises were done in the practical part of the main section of the educational unit for 30 minutes. The researcher used SPSS to analyse the pre- and post-test results and found that skill exercises based on surround vision and visual tracking improve mental rotation and skill performance in the players studied. This study proved the importance of skill exercises based on surround vision and visual tracking in developing mental rotation and futsal skill performance, therefore coaches and futsal specialists should take its findings to heart.